ROLE OF THERAPEUTIC EXERCISES IN NEUROGENIC THORACIC OUTLET SYNDROME - Hanif, Saquib; Tassadaq, Noreen; Rathore, M. Farooq Azam; Rashid, Pervaiz; Ahmed, Nadeem; Niazi, Farooq (Journal of Ayub Medical College Abbottabad, 2007)
Background: Neurogenic Thoracic Outlet Syndrome (TOS) is a set of signs and symptoms existing due to compression of brachial plexus in the cervical area. We performed the study to highlight the role of therapeutic exercises on patients with neurogenic thoracic Outlet Syndrome. Methods: This quasi-experimental study was carried out at Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi. Fifty consecutive patients of neurogenic TOS of both genders and all ages were selected. Patients were diagnosed clinically and the diagnosis was confirmed by electrodiagnosis. These patients were asked to follow a therapeutic exercises program for 6 months. Outcome measures included Visual Analogue Scale (VAS) and Ulnar Nerve Conduction Velocity across neck. Results were compared by applying relevant tests of significance on follow up visits at 3 and 6 months. Results: Mean age was 39.1±7.79 years. Thirty seven (74%) cases were females and thirteen (26%) were males. On each visit, statistical analysis showed significant improvement with therapeutic exercises. After 6 months of conservative treatment, 17 (34%) of patients showed full recovery, 14 (28%) had marked improvement, 16 (32%) had partial improvement while 3 (6%) patients reported with persistent severe symptoms. Conclusion: Current study shows that a trial of therapeutic exercises provides relief of symptoms of Neurogenic Thoracic Outlet Syndrome in majority of patients. Key Words: Thoracic Outlet Syndrome, entrapment syndromes, Electrodiagnosis, Therapeutic Exercises, Rehabilitation